Arsenophonus and Sodalis Symbionts in Louse Flies: an Analogy to the Wigglesworthia and Sodalis System in Tsetse Flies - Nováková, Eva; Husník, Filip; Šochová, Eva; Hypša, Václav (Applied and environmental microbiology, 2015)
Symbiosis between insects and bacteria result in a variety of arrangements, genomic modifications, and metabolic interconnections. Here, we present genomic, phylogenetic, and morphological characteristics of a symbiotic system associated with Melophagus ovinus, a member of the blood-feeding family Hippoboscidae. The system comprises four unrelated bacteria representing different stages in symbiosis evolution, from typical obligate mutualists inhabiting bacteriomes to freely associated commensals and parasites. Interestingly, the whole system provides a remarkable analogy to the association between Glossina and its symbiotic bacteria. In both, the symbiotic systems are composed of an obligate symbiont and two facultative intracellular associates, Sodalis and Wolbachia. In addition, extracellular Bartonella resides in the gut of Melophagus. However, the phylogenetic origins of the two obligate mutualist symbionts differ. In Glossina, the mutualistic Wigglesworthia appears to be a relatively isolated symbiotic lineage, whereas in Melophagus, the obligate symbiont originated within the widely distributed Arsenophonus cluster. Although phylogenetically distant, the two obligate symbionts display several remarkably similar traits (e.g., transmission via the host's "milk glands" or similar pattern of genome reduction). To obtain better insight into the biology and possible role of the M. ovinus obligate symbiont, "Candidatus Arsenophonus melophagi," we performed several comparisons of its gene content based on assignments of the Cluster of Orthologous Genes (COG). Using this criterion, we show that within a set of 44 primary and secondary symbionts, "Ca. Arsenophonus melophagi" is most similar to Wigglesworthia. On the other hand, these two bacteria also display interesting differences, such as absence of flagellar genes in Arsenophonus and their presence in Wigglesworthia. This finding implies that a flagellum is not essential for bacterial transmission via milk glands.
Keywords: genom bakteriální; DNA bakterií; Phylogeny; Phthiraptera; mikroskopie; Sequence Homology; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Cluster Analysis; symbióza; zvířata; Enterobacteriaceae; Symbiosis; sekvenční analýza DNA; DNA, Bacterial; fylogeneze; shluková analýza; moucha tse-tse; Tsetse Flies; Animals; Genome, Bacterial; Microscopy; sekvenční homologie